Киши жастағы балалардың логикалық ойлаўын раўажландырыўда қарақалпақ халық аўыз еки дөретпелериниң тутқан орны (FAN va JAMIYAT, 2021)
The article deals with one the most impontant problems of up-bringing children of preschool age and the influence of works of Karakalpak folklore as fairy tales, riddles, twisters, proverbs and sayings, children‘s poem‘s and phymes onto children‘s psychology. Their educational role are revealed on the base of theoretical and historical aspecta of pedagogics.